Differential selection of multidrug efflux systems by quinolones in Pseudomonas aeruginosa. - Köhler, T (1997)
Resistance mechanisms selected after in vitro exposure to 12 quinolones were analyzed for Pseudomonas aeruginosa. Efflux-type mutants were predominant. Quinolones differed in their ability to select a particular efflux system. While the newer fluoroquinolones favored the MexCD-OprJ system, the older quinolones selected exclusively the MexEF-OprN or MexAB-OprM systems. A protonable C-7 substituent in combination with a C-6 fluorine atom is a structural determinant of quinolones involved in efflux pump substrate specificity.